Edukasi Pemanfaatan Daun Kapulaga terhadap Tambak Udang di Desa Sikhorilafau - Dumartina Hutauruk; Manahan Situmorang; Suharyanisa Suharyanisa; Yanti Musyawarah (Jurnal Nusantara Berbakti, 2025)
The many negative effects on the use of chemical-based medicine have made researchers increasingly interested in looking for alternative natural ingredients that have high therapeutic potential and minimal side effects. One of the plants that is often used as a medicinal ingredient is cardamom (Amomum cardamomum L.), which comes from the Zingiberaceae family. Cardamom has been widely used by the community as an aromatic, carmimental (reducing gas in the stomach), cough medicine, mouth freshener, and various other traditional medicines. The content of bioactive compounds such as alkaloids, flavonoids, tannins, and saponins in cardamom is believed to play an important role in providing pharmacological effects. This study aims to analyze the bioactivity level of toxicity of cardamom leaf ethanol extract against shrimp larvae Artemia salina L. using the Brine Shrimp Lethality Test (BSLT) method and determine the LC₅₀ value as a toxicity parameter. The research method used an experimental quantitative approach with six treatment concentrations, namely 25 ppm, 50 ppm, 100 ppm, 200 ppm, 500 ppm, and 1000 ppm, as well as one negative control. Each treatment was replicated five times to get accurate results. A total of 350 Artemia salina larvae were used, with 10 larvae for each concentration test. Larval mortality was calculated after 24 hours of treatment to determine the potential toxicity of the extract. In addition to laboratory research, community service programs are carried out to increase coastal communities' understanding of the use of cardamom leaves for pond shrimp larvae. This education is important because the results of the research are expected to be the basis for the use of natural materials that are safer, more environmentally friendly, and sustainable in the management of shrimp ponds.